A robust permutation test for the concordance correlation coefficient. (17th February 2021) - Hutson, Alan D.; Yu, Han
Abstract: In this work, we developed a robust permutation test for the concordance correlation coefficient ( ρ c ) for testing the general hypothesis H 0  :  ρ c  =  ρ c (0) . The proposed test is based on an appropriately studentized statistic. Theoretically, the test is proven to be asymptotically valid in the general setting when two paired variables are uncorrelated but dependent. This desired property was demonstrated across a range of distributional assumptions and sample sizes in simulation studies, where the test exhibits robust type I error control in all settings tested, even when the sample size is small. We demonstrated the application of this test in two real world examples across cardiac output measurements and endocardiographic imaging.